2021
DOI: 10.3390/jcm10122551
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic–Pituitary Diseases and Erectile Dysfunction

Abstract: Several hormones contribute to ensure penile erection, a neurovascular phenomenon in which nitric oxide plays a major role. Erectile dysfunction (ED), which is defined as the persistent inability to obtain or maintain penile erection sufficient for a satisfactory sexual performance, may be due to arteriogenic, neurogenic, iatrogenic, but also endocrinological causes. The hypothalamus–pituitary axis plays a central role in the endocrine system and represents a fundamental link between the brain and peripheral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 73 publications
0
17
0
1
Order By: Relevance
“…Interestingly, GH levels at diagnosis and IGF-I levels at evaluation and disease control status have been found not to significantly impact sexual function. A strong link between GH and IGF-I excess and sexual dysfunction in men has been extensively elucidated (21,(57)(58)(59)(60)(61)(62). The co-existence of hypogonadotropic hypogonadism due to tumour mass effect or treatments for acromegaly, such as neurosurgery and/or radiotherapy, and high levels of GH and IGF-I has been reported to alter the regular pulsatility of the gonadotropin secretion at the hypothalamic-pituitary level (57), thus contributing to the pathogenesis of erectile dysfunction as the expression of worse sexual health (21,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, GH levels at diagnosis and IGF-I levels at evaluation and disease control status have been found not to significantly impact sexual function. A strong link between GH and IGF-I excess and sexual dysfunction in men has been extensively elucidated (21,(57)(58)(59)(60)(61)(62). The co-existence of hypogonadotropic hypogonadism due to tumour mass effect or treatments for acromegaly, such as neurosurgery and/or radiotherapy, and high levels of GH and IGF-I has been reported to alter the regular pulsatility of the gonadotropin secretion at the hypothalamic-pituitary level (57), thus contributing to the pathogenesis of erectile dysfunction as the expression of worse sexual health (21,(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…A strong link between GH and IGF-I excess and sexual dysfunction in men has been extensively elucidated (21,(57)(58)(59)(60)(61)(62). The co-existence of hypogonadotropic hypogonadism due to tumour mass effect or treatments for acromegaly, such as neurosurgery and/or radiotherapy, and high levels of GH and IGF-I has been reported to alter the regular pulsatility of the gonadotropin secretion at the hypothalamic-pituitary level (57), thus contributing to the pathogenesis of erectile dysfunction as the expression of worse sexual health (21,(58)(59)(60). Concomitant cardiovascular, such as arterial hypertension and endothelial dysfunction, respiratory, mainly OSAS, and metabolic complications, including abnormalities in glucose and lipid profile leading to insulin resistance, diabetes mellitus and dyslipidemia, may further compromise erectile function and induce a decrease of desire and arousability in acromegaly (21,58,60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypopituitarism (including central hypogonadism), reported in 10–80% of acromegalic cases, and hyperprolactinemia (affecting more than one third of the patients) are associated with a higher rate of subfertility/infertility in acromegalic patients when compared to a non-acromegalic population of the same age, in both females and males [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Pituitary insufficiency and increased prolactin status are related to larger tumors; 90–95% of pituitary GH secreting tumors are macroadenomas; the additional negative role concerning fertility status is caused by secondary DM [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. For instance, one study from 2022 on 529 acromegalic individuals identified a rate of hyperprolactinemia of 39.1% and a prevalence of hypopituitarism of 34.8%, with the gonadal axis being the most affected pituitary axis; there was a hypogonadism frequency of 29.7% [ 45 ].…”
Section: Sub/infertility Issues In Acromegalymentioning
confidence: 99%
“…It is well established that the dysregulation of the hypothalamo-pituitary-adrenal (HPA) axis is involved in the pathogenesis of mood disorders [ 80 ] and sexual dysfunction [ 81 ]. Overall, glucocorticoids regulation is exerted on hypothalamic corticotropin-releasing factor (CRF) neurons in the PVN [ 82 ] and on other central regions, including the hippocampus and amygdala [ 83 ].…”
Section: Lithium and Sexual Dysfunctionmentioning
confidence: 99%